The power of the Internet of Things in Education: an overview of current status and potential - Moreira, Filipe T. (2020)
This paper aims at discussing the potential and analyze main challenges concerning the use of the Internet of Things in education, based on an overview of the literature and the identification of some relevant technologies and projects. The integration of Internet of Things technologies, including open data, in schoolbooks, identified in this context as smartbooks, is also address. Regarding open data, a set of data sources is drawn and possible scenarios for integrating these data into the manuals are discuss. It is concluded that although the Internet of Things presents the potential to facilitate access to real and constantly updated data, there is still a long way to go in this field, namely, in primary and secondary education.